(untitled) (Pedagogy of Higher and Secondary Education, 2012)
У статті розглянуто питання застосування технологій відкритої освіти та дистанційного навчання у зарубіжних країнах, а також визначено роль у використанні цих технологій у процесах модернізації освіти. Ключові слова: відкрита освіта, дистанційне навчання, інформаційно-комунікаційні технології, педагогічні технології, інформаційні технології. The issues of open education and distance learning technologies application in the foreign countries are examined and the role of these technologies in the process of educational modernization is determined in the article. Key words: open education, distance learning, information and communication technologies, pedagogical technologies, information technologies.